β-Cyclodextrin-Mediated Beany Flavor Masking and Textural Modification of an Isolated Soy Protein-Based Yuba Film - Eun-Jung Lee; Honggyun Kim; Jong Yeop Lee; Karna Ramachandraiah; Geun-Pyo Hong (Foods, 2020)
The application of β-cyclodextrin (CD) to remove unattractive volatile compounds has been applied in various food products. This study investigated the effect of CD concentration (1–4%) on the beany flavor masking and textural modification of yuba film prepared by isolated soy protein (ISP) in the presence of (+CD), or after removing, the flavor-entrapped CD (−CD). Based on gas chromatography–mass spectrometry (GC–MS), the addition of CD caused a decrease in 1-octen-3-ol, benzaldehyde, hexanal, and 2-heptanone, which are characterized as the major beany flavor compounds. Regardless of presence or removal, the use of CD was effective in reducing beany flavor in yuba film. Scanning electron microscopy (SEM) observation indicated that the CD present in yuba film was distributed on the lower surface and matrices of the films. In yuba film containing 4% CD, the CD crystals were concentrated on both the upper and lower surfaces of the film. The textural properties of the yuba film were affected by the presence or removal of CD, and better puncture strength was obtained when yuba was made after removing the CD. Therefore, this study indicates that the addition of CD was a good approach to mask the beany flavor of soy protein-based products, and textural properties could be improved by removing CD from the product formulation.